Tinjauan Fiqh Siyasah Terhadap Putusan Mahkamah Konstitusi No. 90/PUU-XXI/2023 Tentang batas Usia Capres dan Cawapres - Wahyuni Dekananda, Atika; Syahputra, Akmaluddin (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The Constitutional Court in Decision Number 90/PUU-XXI/2023 examines the qualifications stipulated in Article 169 letter (q) of Law Number 7 of 2017 concerning the General Elections for the President and Vice President Candidates. This study aims to examine how the interpretation of Fiqh Siyasah relates to the Constitutional Court Decision No. 90/PUU-XXI/2023 regarding the age limits of presidential and vice-presidential candidates. The research method used in this journal is normative juridical research techniques. The research findings show an analysis of Siy?sah qa?h?'iyyah's assessment of Constitutional Court Decision Number 90/PUU-XXI/2023 regarding the age limits of presidential and vice-presidential candidates. This can be equated with the authority of Wil?yah al-ma?h?lim in addressing injustices, arbitrariness, and abuse of authority by the authorities towards their society. Provisions regarding the inability of the Constitutional Court (MK) to decide on matters related to family interests must be more precisely and firmly regulated in relation to such issues. Solutions to Constitutional Court decisions (MK) due to violations of the code of ethics or legal issues are needed. Legal efforts must include improvements by the People's Representative Council (DPR) or reconsideration by the Constitutional Court (MK), excluding judges who have violated the code of ethics. Constitutional Court Decision Number 90/Puu-XXI/2023 which imposes age limits on presidential and vice-presidential candidates is considered to violate the Code of Ethics of the Constitutional Court.